2003
DOI: 10.1016/s0092-8674(03)00429-x
|View full text |Cite
|
Sign up to set email alerts
|

Inducers of Plant Systemic Acquired Resistance Regulate NPR1 Function through Redox Changes

Abstract: NPR1 is an essential regulator of plant systemic acquired resistance (SAR), which confers immunity to a broad-spectrum of pathogens. SAR induction results in accumulation of the signal molecule salicylic acid (SA), which induces defense gene expression via activation of NPR1. We found that in an uninduced state, NPR1 is present as an oligomer formed through intermolecular disulfide bonds. Upon SAR induction, a biphasic change in cellular reduction potential occurs, resulting in reduction of NPR1 to a monomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
1,203
2
19

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,344 publications
(1,302 citation statements)
references
References 44 publications
43
1,203
2
19
Order By: Relevance
“…Under unchallenged conditions, NPR1 protein exists as an oligomer and is excluded from the nucleus. When SAR is induced, monomeric NPR1 is formed, which accumulates in the nucleus and activates the expression of PR genes [20]. In addition to its role in SAR, NPR1 functions in crosstalk between SA-and JA-dependent defense signaling pathways (review see [28]).…”
Section: Regulation Of Production Of Herbivore-induced Air-borne Mesamentioning
confidence: 99%
“…Under unchallenged conditions, NPR1 protein exists as an oligomer and is excluded from the nucleus. When SAR is induced, monomeric NPR1 is formed, which accumulates in the nucleus and activates the expression of PR genes [20]. In addition to its role in SAR, NPR1 functions in crosstalk between SA-and JA-dependent defense signaling pathways (review see [28]).…”
Section: Regulation Of Production Of Herbivore-induced Air-borne Mesamentioning
confidence: 99%
“…The translocation of NPR1 from the cytosol to the nucleus is a critical regulatory step in PR gene expression. Monomerization of the oligomeric protein, which is localized in the cytosol, together with changes in the thiol-disulfide status and nitrosylation of the NPR1 protein are important for the movement into the nucleus [50][51][52][53]. SA-induced changes in cellular redox status trigger the reduction of the disulfide bonds on the NPR1 [51].…”
Section: Redox Regulation Of Npr1 and Related Proteinsmentioning
confidence: 99%
“…After pathogen infection, these disulfide bonds are reduced allowing monomeric NPR1 to translocate to the nucleus where it exerts its co-activator function on many target genes (29). The complexity of this process was further revealed in a subsequent study where the authors showed that S-nitrosylation of NPR1 promoted its oligomerization and thus blunted its transcriptional activity (40).…”
Section: S-nitrosylation Of Plant Defense-related Proteinsmentioning
confidence: 99%